Postcolonial Oceans Contradictions, Heterogeneities, Knowledges, Materialities - Chatterjee, Sukla; Chojnicka, Joanna; Hornidge, Anna-Katharina; Knopf, Kerstin (Anglophone Postcolonial Studies, 2023)
This book contributes to the study of oceans, seas, coastal waters, and rivers within blue humanities by broadening, circulating, and interweaving knowledge about such waters, ocean epistemologies, and sea narratives from pluriversal epistemological, geographical, cultural, and disciplinary perspectives. The contributors from Africa, Asia, the Caribbean, Europe, North America and the Pacific explore the interconnections between oceans, coastal areas, rivers, humans, animals, plants, organisms, and landscapes in the fields of cultural history and cultural studies, critical race and postcolonial studies, marine and environmental studies, linguistics, literature, film and media studies.